(3ddOYGhi GdJLGQjIs - (3Ydj YhV(B, (3MSfs ((3GdGScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2003)
(3GdJLGQI HhLg YGe GdGYeGd GdJLGQjI , GdJGLQ , GdeJLQ , GdSLd GdJLGQj , GdOaJQ GdJLGQjI , Shb GdGhQGb GdeGdjI GdGdJRGe hGdYbhO hGdJLGQjI dGYPGQ hOYGhj GdeSDdjI , fbd GdJcfhdhLjG , GdHjhY GdJLGQjI , GdQgf GdJLGQj GdhcGdI GdJLGQjI GdSeSQI , Gdfbd GdHQj hGdHMQj hGdLhj WHbG ddbGfhf GdJLGQI GdLOjO, YedjGJ GdHfhc ,OYGhj hWYhf GdVQGFH , GdGhQGb GdJLGQjI , GdceHjGdI GdTjc , GdSfO dGeQ GdGadGS hGdUdM GdhGbj efg, GdUjZ aj JTQjYGJ MeGjI GdedcjI GdacQjI GdbGfhf Qbe (B82 (3dSfI (B2002 (3, GdUjZ aj GdTQcGJ GdJLGQjI UjZ GdGSJAfGa hGdfbV aj GdehGO GdJLGQjI hGdHMQjI hGdVQGFHs
Keywords: (3GdbGfhf GdJLGQjs